Hollow cathode discharge in low pressure oxygen: transient mode - Bazhenov, V.Yu.; Matsevich, S.V.; Piun, V.M.; Tsiolko, V.V. (Вопросы атомной науки и техники, 2015)
Glow characteristics of the discharge with cylindrical hollow cathode at oxygen pressure in a range of 0.015…0.09 Torr are determined. Dependencies of radial electric field in the plasma on the discharge parameters are defined, and particular fact of creation at pressure higher than ~ 0.06 Torr the potential barrier at the boundary between negative glow plasma and cathode layer, which limits ion escaping to the cathode. As well, limits of the discharge glow characteristics are determined, which result in appearance of the hollow cathode effect.